(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
Patriotism is one of the spiritual values that becomes more important as the society develops. Patriotism is a characteristic characteristic of persons who deeply respect the history and destiny of the motherland, people, and are able to show examples of selflessness in the interests of the Motherland. The feeling of respect, love, and trust for the country and the people is formed on the basis of certain common interests and goals, takes a deep place in the hearts of people, and affects their activities.